ASSESSMENT OF THE AVERAGE DAILY DIETS OF PROFESSIONAL ATHLETES ON ACTUAL AND ALTERED DIETARY BACKGROUNDS - Хидиров Неъмат Чоршанбиевич; Тухтаров Бахром Эшназарович; Валиева Мархабо Усмоновна (Galaxy International Interdisciplinary Research Journal, 2023)
It is known that the biological value of diets characterizes the strength of biological effects on a living organism and consists of the sum of the biological value of proteins, lipids, vitamins, biomicroelements and other biologically active substances [1,2,3]. The purpose of the research was to select the best options for the average daily norms of a set of products for professional athletes of Uzbekistan.